The trust levels of Omani public school principals and their distributive leadership as perceived by their teachers - Aieman Ahmad Al-Omari; Yara Yasir Hilal (International Journal of Education and Learning, 2022)
Evaluating the relationship between the different components of distributive leadership help researchers and practitioners understand strength of relationships and potentially insight into how they are related with trust levels. The research aims at studying the trust levels of public-school principals in Oman and their distributive leadership as perceived by their teachers in Sultanate of Oman. The study adopts a quantitative research methodology were data was collected using the teacher trust in administration survey with 10 items, and the IB world school distributed leadership survey. A total of 201 teachers participated in the study. The study results indicated that the level of trust level was in moderate level that reported by teachers. All of the dimensions of distributed leadership were in moderate level. The correlation test showed that there was significant positive correlation trust level and all dimensions of distributed leadership. High level of correlation was between “school organization” and trust level (r=.891). Future research may also be explored, focusing on building trust between school leaders and teachers.